UPAYA PENCEGAHAN STUNTING PADA IBU HAMIL DAN BALITA DI DESA SUMBER TANI - Tara Arini; Rizky Octaviani Aulia Hutabarat; Seva Maya Sari (STKIP Subang, 2024)
Stunting is a chronic nutritional problem that affects the growth and development of children, especially in developing countries such as Indonesia. Stunting prevention has become a national health priority, considering its negative impacts not only on physical, but also cognitive development of children in the future. This study aims to increase awareness of pregnant women about stunting prevention through an education program implemented in Sumber Tani Village, Batubara. This education involved 15 pregnant women, who received training on early detection of stunting and how to prevent it. The results showed a significant increase in pregnant women's knowledge about stunting after training, with all participants having an adequate understanding of stunting prevention. This program emphasizes the importance of health monitoring during pregnancy, balanced nutritional intake, and iron supplementation. Support from various parties, including health workers and the village government, is also key to the success of this program. Through joint efforts, it is hoped that the prevalence of stunting can be reduced significantly, thereby creating a healthier and smarter generation).